(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
In this study we describe the phytofabrication of AgNps through a green route as a cost-effective, instantaneous and an eco-friendly approach using Petrea volubilis L. stem broth. The influence of physico-chemical parameters - contact time, stem broth quantity, pH, temperature, and silver nitrate concentration were studied and optimised to engineer, nanoparticles of diverse sizes. Nanoparticles were characterized by UV-Vis spectroscopy, FTIR, XRD, Zeta potential, EDS, and HRTEM. The characterization using HRTEM showed that, the nanoparticles were spherical and with increase in contact time, stem broth quantity, pH, and temperature, the NPs size minimised whereas escalation in silver nitrate concentration, increased their size. Capping molecules were negatively charged and the NPs were passably stable according to zeta potential readings and they were crystalline as per XRD data. According to FTIR analysis, the bio reduction was attributed to alcohol, ethers, carboxylic acids, and esters. The highest anti-bacterial activity was observed against S. aureus and S. typhi whose ZOI diameter was 13 mm at 100μl in both bacteria. The highest anti-fungal activity of silver nanoparticles was observed against A. flavus whose ZOI diameter was 9 mm at 100μl compared to P. chrysogenum which is 3 mm at 100μl. The stem broth did not show any anti-microbial activity for the microbes. Anti-microbial activity of AgNPs is due to its small size and high surface area. Our findings clearly discloses that sizes of silver nanoparticles can be varied by varying the physico-chemical parameters and the small sized nanoparticles so formed are promising antimicrobial agents and has a great potential in various medical applications.